Packing random graphs and hypergraphs. Issue 1 (1st November 2016) - Bollobás, Béla; Janson, Svante; Scott, Alex
Abstract : We determine to within a constant factor the threshold for the property that two random k ‐uniform hypergraphs with edge probability p have an edge‐disjoint packing into the same vertex set. More generally, we allow the hypergraphs to have different densities. In the graph case, we prove a stronger result, on packing a random graph with a fixed graph. © 2016 Wiley Periodicals, Inc. Random Struct. Alg., 51, 3–13, 2017